Literaturnaia programma . Literaturnaia programma . Literary Program . Литературная программа - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program on the family of philanthropists Lazarevs, about Decembrists Peter Svistunov and about writer IUrii Dombrovskii. Передача рассказывает о семье меценатов Лазаревых, о декабристе Петре Свистунове и о писателе Юрии Домбровском.